2014
DOI: 10.3389/fmicb.2014.00240
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of bacteria packaging by protozoa in the persistence and transmission of pathogenic bacteria

Abstract: Many pathogenic bacteria live in close association with protozoa. These unicellular eukaryotic microorganisms are ubiquitous in various environments. A number of protozoa such as amoebae and ciliates ingest pathogenic bacteria, package them usually in membrane structures, and then release them into the environment. Packaged bacteria are more resistant to various stresses and are more apt to survive than free bacteria. New evidence indicates that protozoa and not bacteria control the packaging process. It is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 104 publications
1
55
2
2
Order By: Relevance
“…pneumoniae, E. aerogenes, R. terrigena, and R. ornitholytica. Previous data demonstrated that Enterobacteriaceae can survive and multiply within amoeba host [23,[35][36][37][38][39] which is consistent with our findings. At 48h co-incubation, the intracellular counts for all bacteria in our study decreased onwards.…”
Section: Co-culture Of a Spelaea And Bacteriasupporting
confidence: 93%
“…pneumoniae, E. aerogenes, R. terrigena, and R. ornitholytica. Previous data demonstrated that Enterobacteriaceae can survive and multiply within amoeba host [23,[35][36][37][38][39] which is consistent with our findings. At 48h co-incubation, the intracellular counts for all bacteria in our study decreased onwards.…”
Section: Co-culture Of a Spelaea And Bacteriasupporting
confidence: 93%
“…Without V-ATPase at the LCV, the vacuole fails to acidify, the lack of a proton gradient prevents lysosomal enzymes from functioning, and there is a lack of ability to transport ions for metal poisoning, all involved in bacterial killing. shown to be released via pellets Denoncourt et al, 2014;Faulkner et al, 2008;Gardunow et al, 2008). Post-lysosomal compartments of other protists are formed but have not been well studied (Stewart & Weisman, 1972).…”
Section: Phagotrophy By Protists Versus Phagocytosismentioning
confidence: 99%
“…Because the molecular basis of phagocytosis is conserved between 49 amoebae and mammals, many bacteria that can evade intracellular killing and replicate inside 50 immune phagocytes also infect and kill free-living amoebae [12,13]. Indeed, amoebae are 51 thought to be the primary reservoir for these bacterial pathogens in nature and potentially a 52 natural predator that selected for their pathogenic features [14][15][16][17][18][19][20]. 53 54 Phagocytosis is a specific process, requiring host receptors that recognize and bind ligands on 55 the bacterial cell surface [21][22][23][24][25].…”
Section: Background 33 34mentioning
confidence: 99%